Potensi Penghambatan Sel Kanker Paru Dari Ekstrak Davallia denticulata - Hendra, Rudi; Afham, Muhammad; Khodijah, Rohimatul (Pengurus Pusat Ikatan Apoteker Indonesia, 2021)
An epiphytic fern known as Davalia denticulata, which is a member of the Davalliaceae family, grows on oil palm. It has been reported that several different species within this genus have been used as anticancer agents, antimicrobial agents, and antioxidants. However, there has been no report of any biological activity associated with this species. As a result, the purpose of this study was to extract secondary metabolites and assess the cytotoxicity of the extracts. The maceration method was used to extract this plant with a variety of solvents (methanol, ethyl acetate, and n-hexane), and the MTS assay was utilized to determine the cytotoxicity of this plant in relation to lung cancer (A549 cell line). According to the findings, the extracts exhibited a wide variety of activity toward the A549 cell line. The IC50 for the activity of the ethyl acetate extract was found to be 317.59 ppm, whereas the IC50s for the water and n-hexane extracts were 575.41 and 806.06 ppm, respectively. These observations allow for a better understanding of the cytotoxicity of the species, which can then serve as a foundation for further research into the isolation and bioactivity of secondary metabolites.